Analisa Perbandingan Penggunaan Biaya Bata Ringan Antara Permen PUPR 28/PRT/M/2016 dan Kontraktor PT. PP PERSERO)Tbk - Gantur , Rufina Geanreni ; Suhudi; Wijaya , Handika Setya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
In the construction sector, there are many components inside it. One of them is project management, which can be divided into three parts cost, time, and quality. The budget for a project is called Budget Plan. In general, the cost between budget plan and real implementation is different. Therefore, it is necessary to analyze the comparison between budget plan and real cost implementation, to know the cost difference and the factors causing the difference between the budget plan of the project with budget plan of permen PUPR. Permen PUPR 28/PRT/M/2016 serves as the guidelines to calculate the budget plan. Meanwhile, the implementation budget plan is calculated on the field. The research is conducted by observing the work accomplished on the field, which includes the preparation work and wall?s work. The research shows the difference between the budget plan and real implementation on the field. The cost of project budget plan is Rp 13.655.643 and for the permen PUPR is Rp 12.943.589. The difference between the budget plan of permen PUPR and the one that on the project is Rp 712.055. The factors that causing the differences are wages, cost of the materials, cost of the equipment, different implementation, quantity of the material and worker coefficient